2007
DOI: 10.1111/j.1440-169x.2007.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of mesenchymal cell fated to blastema is necessary for fish fin regeneration

Abstract: Urodeles and fish have higher regeneration ability in a variety of tissues and organs than do other vertebrate species including mammals. Though many studies have aimed at identifying the cellular and molecular basis for regeneration, relatively little is known about the detailed cellular behaviors and involved molecular basis. In the present study, a small molecule inhibitor was used to analyzed the role of phosphoinositide 3-kinase (PI3K) signaling during regeneration. We showed that the inhibitor disrupted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
2
17
1
1
Order By: Relevance
“…2E). Although a previous study has suggested that RE cells are recruited from the proximal epidermal cells (Nakatani et al, 2008), our analysis further showed that many epidermal cells that migrate from the inter-ray region contribute to RE formation.…”
Section: Fate Tracking Of Fn1b + Re Cellscontrasting
confidence: 74%
“…2E). Although a previous study has suggested that RE cells are recruited from the proximal epidermal cells (Nakatani et al, 2008), our analysis further showed that many epidermal cells that migrate from the inter-ray region contribute to RE formation.…”
Section: Fate Tracking Of Fn1b + Re Cellscontrasting
confidence: 74%
“…Previous studies have indicated that muscle cells, mesenchymal cells, cartilage cells, nerve cells and some cells embedded in mandible peristeum, contribute to the blastema formation [15], [19], [33][34]. Our histological observations showed that nucleated blood cells, fibroblasts, fragmented muscle cells and neural crest-derived pigment cells were included in the lower jaw-regenerating blastema.…”
Section: Discussionsupporting
confidence: 57%
“…These steps do not involve local increases in cell proliferation [6], [7]. However, the epidermal cells, several segments away from the amputation plane, proliferate and migrate towards the wound [11], [12]. Subsequently, a group of highly proliferative mesenchymal cells near the amputation site form a structure called the blastema (Figure S1B) [11], [13], [14].…”
Section: Introductionmentioning
confidence: 99%